Evaluation of cytotoxic activity from Temurui (Murraya koenigii [Linn.] Spreng) leaf extracts against HeLa cell line using MTT assay - Ulil Amna; Halimatussakdiah; Puji Wahyuningsih; Nurdin Saidi; Rosnani Nasution (Wolters Kluwer Medknow Publications, 2019)
Temurui (Murraya koenigii [Linn.] Spreng) is a local plant of Aceh. The leaves of M. koenigii are used in most of the local foods as spices. Nowadays, cancer is claimed as the second deadly disease in the world where the number of sufferers increases every year. Cervical cancer (HeLa) is one of the most dominant cancers that happen in developing country, including Indonesia. Some chemotherapeutic agents using synthetic drugs have been used to treat cancer, but they are relatively expensive and cause poisoning that limits their use. Based on literatures, M.koenigii serves the potential secondary metabolites that could be developed as anticancer agent. This study aims to evaluate the cytotoxic activity from three extracts of M. koenigii leaves against HeLa cell line, including hexane, ethyl acetate, and methanol. Methodology used included extraction process, phytochemical screening, and cytotoxicity evaluation. The result showed that all the three extracts demonstrated a potent cytotoxic activity for HeLa cancer cells. Hexane and ethyl acetate showed a very strong cytotoxic effect with CD50 values <1 μg/mL, whereas methanol extract showed cytotoxic effect with CD50 value of 2.25 μg/mL. These results prove the potential of M. koenigii as an anticancer agent.